Crystal structure of dodecaaqua-bis(μ2-4,4′-bipyridine-κ2N:N′)-bis(4,4′-((5-carboxylato-1,3-phenylene)bis(oxy))dibenzoato-κ1O)tricopper(II) - water (1/4), C62H70Cu3N4O32 - Deng Peng; Li Da; Zhou Yan; Ling Zhi-Hong; Li Yue-Ming (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C62H70Cu3N4O32, monoclinic, C2/c (no. 15), a = 44.710(7) Å, b = 12.8847(17) Å, c = 11.9901(18) Å, β = 102.286(13)°, V = 6749.0(17) Å3, Z = 4, Rgt(F) = 0.0618, wRref(F2) = 0.1978, T = 293(2) K.